Pengembangan Modul Materi Ikatan Kimia Berbasis Guided Inquiry (Universitas Negeri Semarang, 2023)
Bonding is an abstract material and has a high level of difficulty. Most students have difficulty in determining the Lewis structure and valence electrons so that facilities are needed that support the learning process and are in accordance with the curriculum that emphasizes guided inquiry learning. The implementation of a learning can be supported by the existence of relevant learning facilities. One of the learning tools that can be used is teaching materials in the form of modules. Research and development aims to determine the feasibility and to investigate the response of students to chemistry learning modules based guided inquiry on chemical bonding material class X. This study uses the Research and Development (RD). Based on the validation of the results obtained material experts 85.26%, media expert results obtained 92.00% with products developed thus expressed very worthy to use. After validation of the product to expert lecturers and chemistry teachers, the product was tested on a small scale to 17 students. The students' responses were obtained with a percentage of 84.14% stated in the very feasible criteria, thus the module developed in the small-scale trial was included in the criteria very suitable for use in the learning process.